Desarrollo de un coagulante a partir de la cáscara de banano para el tratamiento de aguas residuales (2022)
The implementation of coagulants in wastewater treatment corresponds to one of the most frequently used methods due to its high effectiveness. However, there are environmental implications and high costs generated in their production, due to their industrial origin. Due to this situation, it is pertinent to execute processes in which the raw material consists of an agricultural residue, existing in large quantities that significantly reduces the environmental impact; such as the creation of a coagulant from the banana peel, which will not only provide a solution to a problem of waste accumulation, but will also minimize soil, water and air pollution, the bioaccumulation of substances and the deterioration of the environment.